CONSTRAINTS RELATED TO THE CYTOPATHOLOGICAL EXAMINATION THAT FAVOR THE LATE DIAGNOSIS OF CERVICAL CANCER - Layanne Gomes da Silva, Joyce; Caroline de Sousa, Anne; Sybelly Silva Matos, Gyanna; Rolim de Oliveira, Rafaela; Barros de Quental, Ocilma; Amâncio Leônidas de Souza Santos, Mayllon; Silva Oliveira, Geane (Health and Society, 2023)
Cervical cancer, also known as cervical cancer, is a malignant tumor that develops in the cervix, mainly caused by persistent infection by some types of Human Papillomavirus, present among the female population and responsible for high rates of morbidity and mortality. mortality in the world. In women, cervical cancer can be more lethal due to low adherence to health services, as well as the lack of periodic Pap smear. Therefore, knowing the relevance of this theme, this study was developed with the aim of identifying, in the literature, the obstacles related to the Pap smear that favor the late diagnosis of cervical cancer. This is an integrative review carried out in scientific data sources: Scientific Electronic Online Library (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Nursing Database (BDENF). Searches for studies were carried out from June to November 2022. The descriptors selected for the data search were: cervical neoplasms, cervical intraepithelial neoplasia, late diagnosis, all registered in the Health Sciences Descriptors (DECS). As inclusion criteria for the selection of scientific articles we have: articles published from 2017 to 2022, in Portuguese; available and complete articles. Exclusion criteria were: monographs, thesis, dissertation, publications of repeated articles in the databases. From the analysis of the literature, several obstacles that influence the evasion of women from the health systems were evidenced. In this aspect, the literature has shown that female evasion of the cytological examination is directly related to the lack of information about the importance of the Pap smear. Thus, low adherence to routine consultations and cytological examination is considered a predisposing factor for the occurrence of health problems. Such resistance, which is still quite common in primary care services, is a reflection especially of sociocultural and traditional issues that are related to religious beliefs and archaic practices. In this regard, women have been developing home practices to promote self-care. The search for health services and for gynecological consultations, in most cases, is only sought by women when they develop symptoms of pain, vaginal discharge or complaints related to anomalies, bad smell and bleeding. In addition, recent research indicates that women who live in conditions of social vulnerability are more likely to develop diseases. Faced with this reality, health professionals, especially nurses working in primary care, face numerous challenges for the early screening of cervical cancer.